PEMURNIAN HEMATIT DARI RED MUD PT INDONESIA CHEMICAL ALUMINA (ICA) DENGAN VARIASI SUHU KALSINASI - Adhitiyawarman, Adhitiyawarman; Septiriyani, Melia; Zaharah, Titin Anita (Tanjungpura University, 2024)
Red mud is an insoluble fraction of bauxite ore, and it is a waste from bauxite processing into alumina. Red mud contaminated with alkaline substances and therefore poses a danger to the environment and humans. One of the largest bauxite processing companies in West Kalimantan is PT Indonesia Chemical Alumina (ICA). PT ICA can produce red mud around 240.000-450.000 each year. Red mud contains some minerals that are useful for various industries. The largest mineral content in red mud is hematite. Hematite is an iron oxide mineral with the chemical formula Fe2O3. This study aims to determine the hematite content of the extraction results from Red mud PT ICA. This research also investigates how different calcination temperatures during synthesis impact material properties, with analysis using XRF and XRD. It is known that the extracted sample contains 49.74% Fe2O3. The results of XRF analysis show that at 900 °C, the hematite content produced is higher (90.20%) compared to 800 °C (87.84%). The results of XRD analysis show that the position of the typical 2Î¸ peaks of hematite that appear in both temperature variations is not too different, namely: 33.04 °; 35.515; 54.01 ° at 800 °C and 33,06 °; 35,55 °; 54,04 ° at 900 °C. The calcination temperature variation is also known to affect the percentage of hematite crystallinity, which is 18.23% at 800 °C and 24.87% at 900 °C. The crystal structure of hematite is rhombohedral.